Urocortin 2 protects heart and kidney structure and function in an ovine model of acute decompensated heart failure: Comparison with dobutamine. (15th October 2015) - Rademaker, Miriam T.; Ellmers, Leigh J.; Charles, Christopher J.; Mark Richards, A.
Abstract: Background: Renal dysfunction is a frequent complication and crucial determinant of outcome in acute decompensated heart failure (ADHF). The aim of the study was to assess urocortin 2 (Ucn2) as a short-term therapy in ADHF with a focus on its renal effects. Comparison was made with dobutamine to distinguish effects beyond pure inotropism. Methods: Sheep with ADHF received a 2-day infusion of a vehicle-control, Ucn2 or dobutamine (n = 6/grp). Results: Compared to controls, Ucn2 and dobutamine produced matched improvements in cardiac contractility and output and arterial pressure, whereas reductions in central venous and left atrial pressures were greater with Ucn2. Both agents comparably repressed ADHF-activated hormone systems with the exception of the natriuretic peptides, which fell significantly during dobutamine but not Ucn2. While Ucn2 and dobutamine increased creatinine clearance and urine volume similarly, only Ucn2 induced a significant natriuresis. Ucn2 also decreased collagen deposition in the heart and kidney and suppressed gene expression of collagen-1, transforming growth factor-β1, components of the angiotensin system (angiotensinogen, angiotensin-converting enzyme, type-1 receptor) and markers of hypertrophy (GATA binding protein-4, β-myosin heavy chain), apoptosis (caspase3) and inflammation/injury (interleukin-18, cystatin C, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1) in these tissues, while increasing cardiac natriuretic peptide mRNA. In contrast, dobutamine produced reduced or opposite effects on expression of these factors. Conclusions: Ucn2 administration in ADHF has favorable effects on hemodynamics, the natriuretic peptides and tissue mediators of inflammation, fibrosis, apoptosis and hypertrophy that stand in contrast to dobutamine. These data support Ucn2's potential as a renoprotective therapeutic in this setting.